Ultrastructure and morphometry of the egg of Coquillettidia albifera (Prado) with illustrations of male genitalia (Diptera: Culicidae) - Alencar, Jeronimo; Gil-Santana, Hélcio Reinaldo; de Mello, Cecilia Ferreira; Marcondes, Carlos Brisola; Santos-Mallet, Jacenir Reis Dos (Zootaxa, 2019)
The ultrastructure and morphometry of the egg of Coquillettidia albifera (Prado) (Diptera: Culicidae) studied under scanning electronic microscopy is presented for the first time. The identification of the species was confirmed by examination of the genitalia of males collected with females. The male genitalia are redescribed and digital photographs are provided. The eggs are elliptical with the anterior region elongate and tubuliform, length 661 ± 2.59 µm and width 183 ± 2.59 µm (ratio length/width 3.61 ± 0.08). The dorsal surface is covered by a hexagonal, pentagonal and rectangular chorionic network with randomly distributed tubercles. The micropylar disc has a diameter of 18.91 ± 0.65 µm, surrounded by a continuous protuberant collar with a thickness of 4.4 ± 0.3 µm. No structure or vestige of cement related to egg attachment was observed.